The changing business ethics and etiquette, in Slovakia and Hungary, due to globalization - Tóth, Zsuzsanna; Józsa, László; Huszárik, Erika Seres; Fam, Kim-Shyan; Sharipudin, Mohamad-Noor Salehhuddin; Ayub, Suffian Hadi (Obudai Egyetem, Obuda University, 2024)
There are significant differences between the culture, ideology, and values of different nations, so it is not surprising that there are differences in business ethics and etiquette. Therefore, it is essential when establishing and maintaining business relations that the parties get to know each other's ethnic customs or general international etiquette to approach each other with greater understanding and develop more successful business negotiations and business relationships. This paper aims to illustrate the similarities and differences in etiquette behavior, through the examples of two neighboring countries (Slovakia and Hungary). Based on the results of our primary, questionnaire-based, cross-national research, we conclude that companies in both Hungary and Slovakia consider that the manifestations of business ethics in the countries have improved over the last ten years due to globalization.